Disparities in self-rated health across generations and through the life course. (February 2017) - Link, Bruce G.; Susser, Ezra S.; Factor-Litvak, Pam; March, Dana; Kezios, Katrina L.; Lovasi, Gina S.; Rundle, Andrew G.; Suglia, Shakira F.; Fader, Kim M.; Andrews, Howard F.; Johnson, Eileen; Cirillo, Piera M.; et al.
Abstract: Extensive evidence leads us to expect that health disparities by race and socioeconomic status found in one generation might be reproduced in the next. To the extent that this occurs it is important to assess life course processes responsible for the reproduction. Prospective evidence concerning such life course processes is hard to come by as it requires long-term follow-up of individuals from childhood through adult life. We present data from the Child Health and Development Disparities study that provides evidence relevant to this issue with respect to self-rated health. Mothers and offspring recruited in California's Bay Area between 1959 and 1967 were assessed during pregnancy with follow-up exams of offspring along with in-person interviews with mothers (at offspring ages 5, 9–11, 15–17) and offspring (at ages 15–17, ∼50). Available data allow us to assess the importance of three potential life course pathways in the reproduction of inequalities in self-rated health – socioeconomic pathways, cognitive pathways and pathways involving emerging health itself. As expected we found that race and SES disparities in SRH are reproduced across generations. They are evident in mothers, not strong or significant in offspring at 15–17, but present once again in offspring at age ∼50. Concerning potential pathways, we found that indicators of child health were related to adult SRH and played some role in accounting for race but not SES disparities in adult SRH. Cognitive abilities were unrelated to adult SRH with childhood SES controlled. Childhood SES was associated with adult SRH independent of other childhood factors and is reduced to non-significance only when offspring college attainment is controlled. Race and SES disparities in self-reported health in one generation are re-expressed in the next with strongest support for SES pathways in this transmission. Highlights: Prospective life course data to better understand race and SES health disparities. Assesses disparity pathways involving SES, cognitive ability and emerging health. Each pathway plays some role in disparities but SES pathways play the largest role.